Psoriatic Insomnia: A Subjective and Objective Sleep Evaluation - Katerina Vlami; Kleoniki Pantelidi; Maria Dalamaga; Fani Karagianni; Konstantinos Theodoropoulos; Spyridon Papiris; Evangelia Papadavid (Medical Journals Sweden, 2023)
Psoriasis may affect patients' sleep. In order to examine this relationship, this study evaluated non-anxious and non-depressive patients with moderate to severe psoriasis before and after 6 months of systemic treatment. A prospective case-control study with 46 consecutive patients (mean age 51.1 ± 12.8 years, 18 women) and 24 age-, sex- and body mass index-matched controls (mean age 46.5 ± 15.4 years, 12 women) was conducted to assess sleep using both sleep questionnaires and actigraphy. Of psoriatic patients, 91.3% were poor sleepers, and 65.2% of the psoriatic patients presented insomnia symptoms, compared with 54.2% and 33.3% of the control group (p < 0.001, p = 0.02, respectively). Actigraphy showed that Total Sleep Time was shorter in patients, while 82.6% of the psoriatic patients had poor Sleep Efficiency, compared with controls (p = 0.004, p = 0.03, respectively). Patients' quality of life was associated with sleep disturbance (p < 0.001), and pruritus was negatively correlated with sleep duration (p < 0.001). After 6 months of treatment, patients' sleep pattern, according to actigraphy, had not changed significantly; however, they had insomnia for no longer than the control group (p = 0.65), whereas the above-mentioned correlations were non-significant after treatment. Psoriatic insomnia was improved after 6 months of systemic treatment. Actigraphy may be used as an objective tool to evaluate sleep in these patients.